Cross-Ecosystem Linkages: Transfer of Polyunsaturated Fatty Acids From Streams to Riparian Spiders via Emergent Insects - Kowarik, Carmen; Martin-Creuzburg, Dominik; Robinson, Christopher T. (Frontiers in Ecology and Evolution, 2021)
Polyunsaturated fatty acids (PUFAs) are essential resources unequally distributed throughout landscapes. Certain PUFAs, such as eicosapentaenoic acid (EPA), are common in aquatic but scarce in terrestrial ecosystems. In environments with low PUFA availability, meeting nutritional needs requires either adaptations in metabolism to PUFA-poor resources or selective foraging for PUFA-rich resources. Amphibiotic organisms that emerge from aquatic ecosystems represent important resources that can be exploited by predators in adjacent terrestrial habitats. Here, we traced PUFA transfer from streams to terrestrial ecosystems, considering benthic algae as the initial PUFA source, through emergent aquatic insects to riparian spiders. We combined carbon stable isotope and fatty acid analyses to follow food web linkages across the ecosystem boundary and investigated the influence of spider lifestyle (web building vs. ground dwelling), season, and ecosystem degradation on PUFA relations. Our data revealed that riparian spiders consumed considerable amounts of aquatic-derived resources. EPA represented on average 15 % of the total fatty acids in riparian spiders. Season had a strong influence on spider PUFA profiles, with highest EPA contents in spring. Isotope data revealed that web-building spiders contain more aquatic-derived carbon than ground dwelling spiders in spring, although both spider types had similarly high EPA levels. Comparing a natural with an anthropogenically degraded fluvial system revealed higher stearidonic acid (SDA) contents and Σω3/Σω6 ratios in spiders collected along the more natural river in spring but no difference in spider EPA content between systems. PUFA profiles of riparian spiders where distinct from other terrestrial organism and more closely resembled that of emergent aquatic insects (higher Σω3/Σω6 ratio). We show here that the extent to which riparian spiders draw on aquatic PUFA subsidies can vary seasonally and depends on the spider’s lifestyle, highlighting the complexity of aquatic-terrestrial linkages.